Analisis peran komite sekolah dalam peningkatan mutu pendidikan yang berkualitas di SDTQ Al Abidin Surakarta - Harum Dewi Alamsyah Dewi Alamsyah Putri; Peduk Rintayati; Fadhil Purnama Adi (Universitas Sebelas Maret, 2025)
This research aims to describe the role of the school committee in enhancing the quality of education at SDTQ Al Abidin Surakarta. It is a descriptive qualitative study that uses data collection techniques including interviews, observations, and documentation analysis. The data sources for this study include interview results from the school committee chairman, the principal, and teachers, as well as the outcomes of observations and documentation. Data validity was ensured through triangulation. The findings indicate that the school committee's role in improving educational quality has been effectively implemented, resulting in a productive learning environment that supports students' interests and talents, and contributes to the achievement of the school’s vision, mission, and goals.